Central Odontogenic Fibroma of the Mandible - Saeedeh Khajeh Ahmadi; Amin Rahpeyma (Mashhad University of Medical Sciences, 2012)
A 16-years-old female patient with painless swelling of the right side of mandible is described. She noticed the swelling from two years ago, without painful symptoms. Axial CT imaging showed buccal expansion with intact buccal and lingual cortical bone. The report of incisional biopsy was central odontogenic fibroma. Under general anesthesia the lesion was removed after ostectomy of buccal cortical plate and inferior alveolar nerve preserved. Three-year follow-up after tumor excision relieved no recurrence.